Molecular Transport in Thin Thermoresponsive Poly( N -isopropylacrylamide) Brushes with Varying Grafting Density - García, Teodoro Alonso (2012)
The effect of the grafting density on the molecular transport through thermoresponsive brushes of  poly(Nisopropylacrylamide) (PNIPAM) grafted onto flat gold substrates was investigated using voltammetry and impedance spectroscopy. PNIPAM brush layers were synthesized at four different grafting densities using surface-initiated atom transfer radical polymerization (SI-ATRP) from mixed self-assembled monolayers of ω-mercaptoundecyl bromoisobutyrate and undecanethiol chemisorbed on gold surfaces. Tethered PNIPAM layers with grafting densities resulting from initiator concentrations lower than 25% in the thiol monolayer show the same transport properties as the initial self-assembled monolayer before brush synthesis. For higher grafting densities, the diffusion coefficients, D, of the K3[Fe(CN)6]/K4[Fe(CN)6] redox probe is 7 orders of magnitude smaller than those typically measured in aqueous solutions and independent of whether the brush is collapsed or swollen. The collapse of the PNIPAM brush drives a hydrophilic/hydrophobic transition in addition to structural/conformational transformations of the grafted layers, resulting in still smaller values of D. However, these changes do not lead to a blocking effect on the active area of the gold surface, which is only determined by pinholes or discontinuities in the thiol initiator monolayer. These results are only observed for thin PNIPAM brush layers.